2016
DOI: 10.1002/chem.201604762
|View full text |Cite
|
Sign up to set email alerts
|

TiO2‐Supported Re as a General and Chemoselective Heterogeneous Catalyst for Hydrogenation of Carboxylic Acids to Alcohols

Abstract: TiO2-supported Re, Re/TiO2, was found to promote selective hydrogenation of carboxylic acids having aromatic and aliphatic moieties to the corresponding alcohols. Re/TiO2 showed superior results compared to other transition-metal-loaded TiO2 and supported Re catalysts for selective hydrogenation of 3-phenylpropionic acid. 3phenylpropanol was produced in 97% yield under mild conditions (5 MPa H-2 at 140 degrees C). Contrary to typical heterogeneous catalysts, Re/TiO2 does not lead to the formation of dearomatiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
64
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(69 citation statements)
references
References 55 publications
3
64
0
1
Order By: Relevance
“…[17] Accordingly,w ee xamined the relative adsorption affinities of COOCH 3 and benzene moieties on the catalysts urfaceb ye mploying methyla cetate and benzene as probe molecules. We have previously reported that the selectivity of the hydrogenationo fc arboxylic acid derivatives strongly dependso n the relative adsorption affinitieso ftheir functional groups,specifically on the benzene rings and the COOH groups.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[17] Accordingly,w ee xamined the relative adsorption affinities of COOCH 3 and benzene moieties on the catalysts urfaceb ye mploying methyla cetate and benzene as probe molecules. We have previously reported that the selectivity of the hydrogenationo fc arboxylic acid derivatives strongly dependso n the relative adsorption affinitieso ftheir functional groups,specifically on the benzene rings and the COOH groups.…”
Section: Resultsmentioning
confidence: 99%
“…Consequently,ah ighly versatile heterogeneous catalyst for the reduction of ab road variety of carboxylic and carbonic acid derivatives represents ah ighly desirable research target. [17] Notably,t his heterogeneous catalytic system did not produce any dearomatized byproducts, despite the difficulty of hydrogenating the COOH group. [12] Even though various catalysts of this nature have been proposed, [8,12] heterogeneous catalysts normally suffer from competitive product formation as ar esult of dearomatization of the aromatic rings and/or the over-reduction to give alkane products, which diminishes their chemoselectivity compared with homogeneousc atalysts.…”
Section: Introductionmentioning
confidence: 99%
“…Although both low- and high-valent Re species in hetero-multimetallic catalysts such as Re 2 (CO) 10 -Ru 3 (CO) 12 39 , Re 2 (CO) 10 -Rh/Al 2 O 3 39 , Re 2 O 7 -OsO 4 40 , ReO x -Pd/SiO 2 41 , ReO x /TiO 2 42 , and Re/TiO 2 43 have been investigated for CA hydrogenation 23, 33 , the specific role of Re in these catalysts remains unclear. Recent examples of ReO x /TiO 2 and Re/TiO 2 catalysis have shown high alcohol selectivity with a rather limited substrate scope, with diverse Re entities (Re 0 , Re III , Re IV , Re VI , and Re VII , calcined and reduced at 400–500 °C with H 2 ) on TiO 2 determined by XPS analysis 42, 43 .…”
Section: Resultsmentioning
confidence: 99%
“…Recent examples of ReO x /TiO 2 and Re/TiO 2 catalysis have shown high alcohol selectivity with a rather limited substrate scope, with diverse Re entities (Re 0 , Re III , Re IV , Re VI , and Re VII , calcined and reduced at 400–500 °C with H 2 ) on TiO 2 determined by XPS analysis 42, 43 . Even though heterogeneous ReO 3 promotes CA hydrogenation under high H 2 pressure ( P H2  = ca.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation